THE ROLE OF GENERATIVE ARTIFICIAL INTELLIGENCE TECHNOLOGY IN CONTROLLING THE KNOWLEDGE OF UNIVERSITY STUDENTS IN PROGRAMMING - Sagimbayeva А.Е.; Zhaxylykov А.Е.; Shekerbekova Ш.Т.; Zhamkeeva А.Б. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2024)
The article examines the role of generative artificial intelligence (GenAI) technology in assessing students’ knowledge of programming in higher education institutions. In the modern education system, GenAI allows you to develop automated assessment systems, effectively carry out the process of checking the code and providing feedback to students. The article discusses the advantages of GenAI such as automation, objectivity and personification, as well as demonstrates its capabilities and ways of applying it in assessing students’ knowledge. In addition, the ethical and technical problems arising in the process of integrating GenAI technologies into the educational process are considered. As a result, it turns out that GenAI offers a new approach in the field of programming knowledge assessment and contributes to improving the quality of knowledge.